2015
DOI: 10.3171/2014.9.peds14289
|View full text |Cite
|
Sign up to set email alerts
|

Duration of the horizontal decubitus position for prevention of cerebrospinal fluid leakage following transection of a tight filum terminale

Abstract: OBJECT The untethering of a tethered spinal cord in patients with a tight filum terminale is a relatively simple procedure that can prevent or improve neurological symptoms. Postoperatively, patients are usually kept in the horizontal decubitus position to prevent a CSF leak. However, the optimal period for keeping patients flat has not been determined yet. The authors compared 2 cohorts with different periods of horizontal decubitus; one with 72 hours and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…7 Both Chern and Ogiwara found that Post = postintervention; Pre = preintervention. * The p values are as follows: p = 0.02 (preintervention); p = 0.05 (postintervention); and p = 0.0021 (total group).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…7 Both Chern and Ogiwara found that Post = postintervention; Pre = preintervention. * The p values are as follows: p = 0.02 (preintervention); p = 0.05 (postintervention); and p = 0.0021 (total group).…”
Section: Discussionmentioning
confidence: 98%
“…1 Recently, Ogiwara and colleagues 7 reported no CSF leaks in a large population of patients who were kept flat for 72 hours.…”
Section: 27mentioning
confidence: 98%
See 1 more Smart Citation
“…2,14,38 An untethering procedure may be associated with serious complications such as CSF leakage, CSF collection, wound dehiscence, and infection. 19,27,30,31 Despite a vast investigation of preventive interventions for such complications, 4,8,18,21,27 no evidenced-based guideline has yet been published.Although prophylactic administration of acetazolamide and/or bed rest following the intradural operation are acceptably used by both neurosurgeons and orthopedic surgeons, no high-level approved evidence exists regarding whether and how to use these measures.To the best of our knowledge, no randomized trial has assessed the prophylactic effect of acetazolamide in reducing complications following spinal surgeries. Likewise, abbreviations DS = dermal sinus; FF = fatty filum; LMMC = lipomyelomeningocele; SCM = slit cord malformation; TCS = tethered cord syndrome.…”
mentioning
confidence: 99%
“…2,14,38 An untethering procedure may be associated with serious complications such as CSF leakage, CSF collection, wound dehiscence, and infection. 19,27,30,31 Despite a vast investigation of preventive interventions for such complications, 4,8,18,21,27 no evidenced-based guideline has yet been published.…”
mentioning
confidence: 99%